Medium-term outcomes following limb salvage for severe open tibia fracture are similar to trans-tibial amputation. Issue 2 (February 2015) - Penn-Barwell, J.G.; Myatt, R.W.; Bennett, P.M.; Sargeant, I.D.; ,
Abstract: Extremity injuries define the surgical burden of recent conflicts. Current literature is inconclusive when assessing the merits of limb salvage over amputation. The aim of this study was to determine medium term functional outcomes in military casualties undergoing limb salvage for severe open tibia fractures, and compare them to equivalent outcomes for unilateral trans-tibial amputees. Cases of severe open diaphyseal tibia fractures sustained in combat between 2006 and 2010, as described in a previously published series, were contacted. Consenting individuals conducted a brief telephone interview and were asked to complete a SF-36 questionnaire. These results were compared to a similar cohort of 18 military patients who sustained a unilateral trans-tibial amputation between 2004 and 2010. Forty-nine patients with 57 severe open tibia fractures met the inclusion criteria. Telephone follow-up and SF-36 questionnaire data was available for 30 patients (61%). The median follow-up was 4 years (49 months, IQR 39–63). Ten of the 30 patients required revision surgery, three of which involved conversion from initial fixation to a circular frame for non- or mal-union. Twenty-two of the 30 patients (73%) recovered sufficiently to complete an age-standardised basic military fitness test. The median physical component score of SF-36 in the limb salvage group was 46 (IQR 35–54) which was similar to the trans-tibial amputation cohort ( p = 0.3057, Mann–Whitney). Similarly there was no difference in mental component scores between the limb salvage and amputation groups ( p = 0.1595, Mann–Whitney). There was no significant difference in the proportion of patients in either the amputation or limb salvage group reporting pain ( p = 0.1157, Fisher's exact test) or with respect to SF-36 physical pain scores ( p = 0.5258, Mann–Whitney). This study demonstrates that medium term outcomes for military patients are similar following trans-tibial amputation or limb salvage following combat trauma.